Application and types of biological control in oil palm plantation - a survey study among smallholders in Merlimau & Jasin, Malacca - Wan Ibrahim, Zuhaila Nasrin (Faculty of Plantation and Agrotechnology, 2016)
Nowadays, most of smallholder only care about to control the damage of oil palm without realizing the effect on environment and disruption ecosystem. A study was conducted on 52 smallholders in Merlimau & Jasin, Malacca to determine the application and types of biological control in oil palm plantation. Data was collected using random sampling method in order to distributed questionnaires to the smallholders. It is found that majority of the smallholders apply biological control in their oil palm management represent 76.9% while 23.1% not apply the biological control. However, due to the implementation of biological control, this survey also had been identified the types of biological control that give much advantageous. Types of biological control smallholders use are tyto alba, snake, tricoderma and beneficial plant.